Feasibility of a Web‐based Gatekeeper Training: Implications for Suicide Prevention. Issue 5 (27th February 2014) - Lancaster, Paige G.; Moore, J. Taylor; Putter, Stefanie E.; Chen, Peter Y.; Cigularov, Konstantin P.; Baker, Aaron; Quinnett, Paul
<x xml:space="preserve">Abstract</x> Web‐based training programs have advantages such as increased scheduling flexibility and decreased training costs. Yet the feasibility of applying them to injury prevention programs such as suicide prevention gatekeeper training has not been empirically verified. Two studies were conducted to assess the feasibility and effectiveness of a web‐based version of the Question, Persuade, and Refer (QPR) gatekeeper training program. Results of Study 1 revealed that participants in a web‐based training demonstrated significant gains in knowledge of suicide prevention, self‐efficacy for suicide prevention, and behavioral intentions to engage in suicide prevention, as compared to those in a control group. Results of Study 2 further showed that the web‐based training may be as effective as the face‐to‐face QPR training across pre‐ (T1) and post training (T2); however, knowledge, self‐efficacy, and behavioral intentions in both groups generally declined from T2 to 6‐months after the training. Overall, these results provide initial evidence to support the feasibility of adopting web‐based media to deliver gatekeeper training. Moreover, the present findings suggest the need to understand how to maintain gatekeepers' knowledge, confidence, motivation, and skills after training.